2018
DOI: 10.1094/pdis-09-17-1341-re
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Major Ancestors of North American Soybean Cultivars for Resistance to Three Pythium Species that Cause Seedling Blight

Abstract: Pythium seedling blight, which can be caused by a number of Pythium spp., is a disease that affects soybean (Glycine max) in the United States and Canada. Pythium ultimum var. ultimum, one of the most common pathogenic species, is favored by cool, wet conditions in early spring and causes seed decay, root rot, and seedling damping-off. In all, 102 major ancestors of modern North American cultivars and "first progeny" cultivars developed directly from ancestral lines were evaluated for resistance to P. ultimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Several studies have measured resistance toward different Pythium species (Rod et al, 2018;Lerch-Olson et al, 2020) and have identified QDRL, mostly minor, in RIL populations of soybean (Ellis et al, 2013;Stasko et al, 2016;Urrea et al, 2017;Klepadlo et al, 2019;Lin et al, 2018Lin et al, , 2020Scott et al, 2019). Almost all of the studies have shown partial resistance aside from one study by Rosso et al (2008) showing monogenic resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have measured resistance toward different Pythium species (Rod et al, 2018;Lerch-Olson et al, 2020) and have identified QDRL, mostly minor, in RIL populations of soybean (Ellis et al, 2013;Stasko et al, 2016;Urrea et al, 2017;Klepadlo et al, 2019;Lin et al, 2018Lin et al, , 2020Scott et al, 2019). Almost all of the studies have shown partial resistance aside from one study by Rosso et al (2008) showing monogenic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several quantitative disease resistance loci (QDRL) for resistance to P. irregulare (Ellis et al, 2013;Stasko et al, 2016;Lin et al, 2018;Scott et al, 2019), P. aphanidermatum (Urrea et al, 2017), P. ultimum var sporangiiferum (Scott et al, 2019), P. sylvaticum (Lin et al, 2020), and P. ultimum var. ultimum (Rod et al, 2018;Klepadlo et al, 2019;Scott et al, 2019) have been identified using biparental soybean populations. Overall, only minor QDRL have been identified and have explained 4.5-17.8% of the phenotypic variation and are located on most chromosomes within the soybean genome.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been widely used to evaluate resistance to Pythium spp. in diverse grain legumes, including common bean (Campa, Perez‐Vega, Pascual, & Ferreira, 2010), soybean (Rod, Walker, & Bradley, 2018; Urrea, Rupe, Chen, & Rothrock, 2017), and chickpea (Kaiser & Hannan, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…resistance to Pythium spp. in diverse grain legumes, including common bean (Campa, Perez-Vega, Pascual, & Ferreira, 2010), soybean (Rod, Walker, & Bradley, 2018;Urrea, Rupe, Chen, & Rothrock, 2017), and chickpea (Kaiser & Hannan, 1983). The majority of resistant accessions identified in the USDA-NPGS and ICRISAT mini-core collections were desi type, which typically produce smaller seeds than kabuli types (Toker, 2009).…”
Section: Crop Sciencementioning
confidence: 99%
“…Fiskeby III is reported to be more tolerant to a variety of abiotic stresses than most soybean germplasm [24][25][26][27][28]. Two studies have shown Fiskeby III to be tolerant to, though not completely resistant, to FeD stress.…”
Section: Phenotypic Analysesmentioning
confidence: 99%